Yes, because they both contain the variable "x". y and 9x would not be like terms because they don't have the same variable. x and 9x2 would not be like terms because the variables are not raised to the same power.
collect like terms and you get 4x + 5x + 8 - 3 ie 9x +5
2x = 5x - 12First step is to move all the like terms to one side of the equation2x (-5x) = -12-3x = -12Next, we can divide both sides by -3 to get rid of the -3 on the left side(-3x)/-3 = (-12)/-3x = 4
5x - 1 = 24 5x - 1 + 1 = 24 + 1 5x = 25 5x/5 = 25/5 x = 5
5x+10=40 5x+10-10=40-10 5x=30 5x/5=30/5 x=6
It is: 2x and 5x are like terms Addition: 2x+5x = 7x Multiplication: 2x*5x = 10x2
= 53 9x3 + 9x2 + 5x1+ 3x1 27 + 18 + 5 + 3
Like terms are: 5x -7x +2x and 3 -5
5x - 3 + x - 9 = 5x Bring like terms together of the left side: 5x + x - 3 - 9 = 5x Combine like terms: 6x - 12 = 5x Add 12 to both sides: 6x = 5x + 12 Subtract 5x from both sides: x = 12
If you have a expression that goes; 2x + 5x etc etc Simplifying the like terms is 7x 2x and 5x are like terms, but 2y and 2x are not. The variable needs to be the same.
-4
-1x-4-4x= -5x-4so it is -5x-4 -5x - 4this is done by combining like terms.
The expression 4x - 3y - 5x - 2y can be simplified by combining like terms. Like terms have the same variables raised to the same powers. In this case, the x terms are like terms and the y terms are like terms. Combining the x terms, we get -x, and combining the y terms, we get -5y. Therefore, the simplified expression is -x - 5y.
Since 5x is a factor of both terms, divide it. 5x3 + 5x = 5x(x2 + 1)
5x + 6y + 3y - 2x you have to add like terms. add the y terms and then the x terms 9y + 3x this is your answer
When the independent variable is of the same degree. Ex. 3x and -5x are like terms. 6 and 9 are like terms. 7x^2 and 9x^3 are NOT like terms.
That equals x.